ESRA19-0302 Bridge over troubled water? Utility of paravertebral blockade in myocardial bridge unroofing. (30th August 2019) - Boublik, J; Mistry, S; Tsui, B; Boyd, J; Brodt, J; Horn, JL
Abstract : Background and aims: Myocardial bridges are bands of myocardium overlapping coronary arteries. Symptomatic bands require cardiothoracic surgery with sterno- or thoracotomy due to their potential of morbidity. The incidence of chronic pain after thoracotomy and sternotomy are up to 33 and 56%, respectively. Paravertebral blockade (PVB) provides effective analgesia in cardiothoracic surgery. The aim of this retrospective analysis was to investigate the utility in our study population with respect to healthcare resource utilization. Methods: Case series of 98 patients undergoing myocardial bridge unroofing: 72 patients (73.5%) sternotomy and 26 (26.5%) thoracotomy. 38 of the sternotomy patients received no block and 29 received bilateral PVBs, 5 were excluded. In the thoracotomy group, 19 patients received an unilateral PVB, 6 received no blocks, 1 patient was excluded after receiving liposomal Bupivacaine. For data analysis, sternotomy and thoracotomy groups were separated. Study was approved by the IRB of Stanford University. Results: There were no statistically significant demographic differences. Sternotomy patients receiving PVBs had a significantly shorter intensive care unit (ICU) stay (1.37±0.82 days vs 1.60±0.82 days (p=0.02), while total length of stay was unaffected (4.25±0.5 vs 4.6±1.13 days, p 0.07). Thoracotomy patients receiving PVBs had shorter ICU admissions (1.21±0.71 vs 2.2±0.74, p=0.02) and hospitalizations than patients not receiving blocks (3.73±0. vs 4.16±0.75p=0.002). Pain scores and opioid requirement were similar in all groups throughout. Conclusions: Paravertebral blocks are of potential utility in cardiothoracic surgery for myocardial bridge unroofing. Depending on the surgical approach, they facilitate either shorter ICU admissions or shorter ICU and hospital stays and decrease health care resource utilization.